Analisis Laporan Keuangan Perbandingan Kinerja Keuangan Dengan Menggunakan Analisis Rasio Keuangan Perusahaan Makanan Dan Minuman Di Indonesia: Studi Pada PT. Garudafood Putra Putri Jaya Tbk, PT. Campina Ice Cream Industry Tbk, PT. Nestle Indonesia Tbk. Dengan Periode 2019-2023 - Fillah Ardhi; Muhammad Indra Wardana; Patricia Channelia Wea; Cholis Hidayati (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to analyse the financial performance of three food and beverage sub-sector companies in Indonesia, namely PT GarudaFood Putra Putri Jaya Tbk, PT Campina Ice Cream Industry Tbk, and PT Nestlé Indonesia Tbk, during the 2019-2023 period. The analysis was conducted using various financial ratios, including liquidity, activity, solvency, profitability, and market, to compare the operational efficiency and financial stability of each company. The results show that PT Nestlé Indonesia Tbk has the most stable and efficient financial performance, followed by PT GarudaFood Putra Putri Jaya Tbk which shows improved performance, while PT Campina Ice Cream Industry Tbk still faces some challenges in its financial management. These findings provide important insights for investors and company management in making strategic decisions